Impurity control by precipitation in synthetic atmospheric nickel laterite sulfate leach solutions - Mbedzi, Ndishavhelafhi (Curtin University, 2020)
In light of fast depleting nickel sulfide ore reserves and increasing demand for nickel, the future of the nickel industry lies in the hydrometallurgical processing of the relatively abundant low-grade nickel laterite ores. The purification of the leach solutions, however, has proven difficult. Hydroxide and oxidative precipitation processes using a variety of reagents were developed for processing synthetic sulfate solutions simulating nickel laterite leach solutions and nickel and cobalt solutions following iron precipitation process.